‘Ossian fürs Frauenzimmer’? Lengefeld, Günderrode, and the Portuguese Translations of ‘Alcipe’ and Adelaide Prata - Bär, Gerald (2014)
This article examines German and Portuguese Ossian translations by female writers, particularly translations of Dar-thula, one of Macpherson's most popular pieces. Charlotte von Lengefeld's and Karoline von Günderrode's German translations raise the question of whether Ossian was considered a suitable subject for women, offering further insights into the reasons for the astonishing popularity of Macpherson's publications in German-speaking countries. The Portuguese versions of the Marquesa de Alorna and Adelaide Prata and their favourable reviews shed light on their acceptance in nineteenth-century Portugal. Comparison of the different approaches and objectives of these four translators together with the analysis of their different source texts and skills is intended to contribute to debate on translation and gender studies